Konsep Harta dalam Al-Qur’an dan Ḥadis - Muhamad Masrur (Jurnal Hukum Islam, 2017)
Wealth is an object that can be possessed, controlled, cultivated, and transferred, whether tangible or intangible, whether registered or unregistered, either moving object or immovable wealth and economic value. The problem of the position and management of the wealth is very much needed to be examined since many people are misusing their property. This research would like to examine how the concept of property in the Al-Qur'ān and Ḥadīs. The results of this study can be seen that the absolute owner of the treasure is Allah SWT, man is entitled to own wealth but its relative, just a deposit, as a jewelry, test of faith and as provision of worship. Al-Qur'ān and Hadīṡ provide guidance on how to obtain wealth is through controlled objects mubah, transaction contracts, inheritance, syuf'ah, and the right of giving to someone who is religiously regulated. The way to manage and spend the wealth is to determine the priority needs, based on the principle of halal ṭayiban, avoid wasteful and tabdzir, the principle of simplicity, for social allocation, as well as for future allocation.